Binder composition for secondary battery

By using the aqueous emulsion composition binder in a non-aqueous secondary battery, the problem of difficulty in providing high energy density and swelling resistance in the previous technology is solved, and high energy density and excellent service life are achieved , while maintaining good cycle stability.

CN119487080APending Publication Date: 2025-02-18阿科玛股份有限公司
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202380051863.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-06
Filing Date
2023-06-28
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to provide a high energy density and excellent service life for non-aqueous secondary batteries within a wide operating temperature range, while maintaining good swelling resistance in battery solvents.

Method used

An aqueous emulsion composition binder is developed, comprising a copolymer in the form of emulsified particles and anionic surfactant accounting for about 0.5-5% of the dry weight of the copolymer, having a sulfonate group or an acid or salt form thereof. The composition exhibits excellent swelling resistance in the battery solvent.

Benefits of technology

It achieves a high energy density and excellent service life for non-aqueous secondary batteries within a wide operating temperature range, while maintaining good cycle stability and swelling resistance in the battery solvent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005227841470000171
    Figure BDA0005227841470000171
Patent Text Reader

Abstract

An aqueous emulsion composition useful as a binder for non-aqueous battery electrodes is provided. The composition comprises a copolymer and an anionic surfactant comprising a sulfonate group or an acid or salt form thereof. The anionic surfactant is not polymerizable with the copolymer. The copolymer comprises, as polymeric monomers: an ethylenically unsaturated ionic monomer comprising a phosphate or phosphonate group or a salt or acid form thereof; an ethylenically unsaturated ionic monomer comprising a sulfonate group or a salt or acid form thereof; a nonionic monoethylenically unsaturated monomer; optionally an ethylenically unsaturated ionic monomer comprising a carboxylate group or a salt or acid or anhydride form thereof; and optionally a monomer having at least two ethylenic unsaturations. Also provided is a slurry composition comprising the aqueous emulsion composition and an active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a binder composition for an electrode of a non-aqueous secondary battery. A secondary battery is a rechargeable battery. Background Art

[0002] There is growing interest in lightweight, high energy density secondary battery technology. Lithium-ion batteries (LIBs) are already widely used as power sources for many devices, such as consumer electronics, electric vehicles, and power tools. The increasing popularity of zero-emission electric vehicles, especially long-range electric vehicles, requires LIB technology to further improve energy density and durability. In order to improve battery energy density and durability, different components of the battery are being studied. These components include the negative electrode (anode), positive electrode, electrolyte, and separator. Improving electrode capacity has great potential for improving battery energy density, especially if improved binders are used.

[0003] The ongoing industrial trend of increasing battery energy density and developing electrode active materials has brought new challenges to traditional polymer binders. Stable battery cycling at high temperatures is particularly challenging. The swelling of the binder in the battery solvent mixture is an important factor affecting the battery cycling stability and should ideally be controlled within a certain range.

[0004] US 10,957,909 discloses a binder composition comprising phosphoric acid functional groups for non-aqueous battery applications.

[0005] US 9,499,691 discloses an emulsion polymer composition comprising phosphoric acid monomers and carboxylic acid / sulfuric acid monomers and an internal crosslinking agent.

[0006] US 8,318,848 discloses an emulsion polymer composition comprising a phosphoric acid monomer and an unsaturated acidic monomer and a nonionic surfactant.

[0007] US2016 / 0248095 discloses a binder composition for non-aqueous battery applications, comprising an unsaturated carboxylic acid, an internal crosslinking agent and an acetylene glycol compound.

[0008] US2015 / 0361291 discloses a multi-stage emulsion polymer composition comprising a phosphoric acid monomer, a carboxylic acid / sulfuric acid monomer and an internal crosslinking agent.

[0009] US2008 / 0269402 discloses an emulsion polymer composition comprising a phosphoric acid monomer, a sulfuric acid monomer and an internal crosslinking agent.

[0010] JP 2013-168323 discloses a binder composition for a non-aqueous battery, which comprises at least one monomer having an alkoxysilyl group and at least one monomer containing an acidic group.

[0011] JP 2011-243464 discloses a binder composition comprising an unsaturated carboxylic acid and an internal crosslinking agent as essential components for a non-aqueous battery.

[0012] JP H-10298386 discloses a composition for non-aqueous batteries comprising sulfonated polyvinylidene fluoride.

[0013] There is still a need for a binder composition for use in electrodes of non-aqueous secondary batteries, which provides a secondary battery with high energy density and excellent service life over a wide operating temperature range. There is also a need for a binder composition that has enhanced resistance to swelling when exposed to battery solvents to provide a secondary battery with good cycle stability and high energy density. Summary of the invention

[0014] In the present invention, the inventors have developed a binder composition having excellent resistance to swelling in battery solvents. The binder composition of the present invention swells in a battery solvent in a desired amount and / or in an optimized manner.

[0015] An aqueous emulsion composition for non-aqueous battery electrodes is provided. The composition comprises: a) a copolymer in the form of emulsified particles; and b) about 0.5-5 wt % of at least one anionic surfactant, based on the dry weight of the copolymer a). The anionic surfactant b) comprises at least one sulfonate group or its acid or salt form. The anionic surfactant b) is not polymerizable with the copolymer a).

[0016] The copolymer a) comprises as polymerized monomers the following monomers, based on the dry weight of the copolymer:

[0017] i) about 0.1-10% by weight of at least one ethylenically unsaturated ionic monomer comprising at least one functional group selected from the group consisting of phosphate, phosphonate; or acid or salt form thereof;

[0018] ii) about 0.1 to 10 weight percent of at least one ethylenically unsaturated ionic monomer comprising at least one sulfonate group or an acid or salt form thereof;

[0019] iii) about 80 to 99.8 weight percent of at least one nonionic monoethylenically unsaturated monomer;

[0020] iv) optionally about 0-10 weight percent of at least one ethylenically unsaturated ionic monomer comprising at least one functional group selected from the group consisting of a carboxylate, or an acid or salt or anhydride form thereof; and

[0021] v) optionally from about 0 to about 2 weight percent of at least one monomer containing at least two degrees of ethylenic unsaturation.

[0022] A slurry composition for forming an electrode of a non-aqueous secondary battery is also provided. The slurry composition comprises an aqueous emulsion composition and at least one particulate electrode-forming material.

[0023] Also provided is an electrode for a non-aqueous secondary battery. The electrode includes a conductive substrate coated with a slurry composition on at least one surface. DETAILED DESCRIPTION

[0024] As used herein, the term "electrode" refers to a dried layer or coating of an electrode-forming slurry composition cast on a current collector. Generally, an electrode is manufactured by a process comprising casting a slurry or paste of dispersed electrode-forming raw materials and (one or more) binders into a thin layer or coating or film, and then drying the layer or coating or film to form an electrode. This is referred to as an electrode.

[0025] As used herein, the term "electrode assembly" refers to or includes a combination of a current collector and an electrode formed thereon. A slurry or paste of dispersed electrode forming raw materials and (one or more) binders can be cast onto a current collector (e.g., aluminum foil, copper foil, or nickel foil) to form an electrode assembly. The electrode assembly may be further coated with a diaphragm forming slurry, such as alumina and a binder dispersed in water. The diaphragm slurry can be cast simultaneously with the electrode slurry using a dual-mode or multi-mode one-step process in a wet-to-wet process. Alternatively, after the electrode is formed, the diaphragm slurry can be cast onto the electrode, or a self-supporting diaphragm can be adhered to the electrode surface. Therefore, the electrode assembly includes a current collector, a dried electrode film, and an optional diaphragm on the top surface of the electrode.

[0026] As used herein, the term "slurry" refers to a free-flowing pumpable suspension of fine solid materials and a binder in water. Such fine solids may include solid particles of electrochemically active materials and conductive materials, which are usually necessary to form electrodes of secondary batteries, as well as polymer binder particles, etc. Various additives may also be dissolved in the water, such as dispersants for improving the dispersion quality of the fine solid materials.

[0027] The composition used as an electrode can be deposited by any method known in the art. Non-limiting examples of such application methods include spraying, roller coating, draw bar application, bird bar application, gravure printing, slot coating or other coil coating methods. The composition is optionally dried with heating. Before or after the drying step, the coating of the composition is optionally rolled to remove moisture and any other volatile materials. The drying time, temperature and any vacuum can be adjusted to achieve the desired drying.

[0028] The structure of the current collector can be mesh, foam, foil, rod or other forms that do not affect the function of the current collector. The current collector material varies depending on whether the electrode is positive or negative. The most common current collector for the negative electrode is aluminum (Al 0 ), copper (Cu 0 ) or nickel (Ni 0 ) Metal sheet or foil. The electrode material is applied and adhered to the surface of the current collector of the lithium ion battery.

[0029] Described herein is an aqueous emulsion composition for non-aqueous battery electrodes, the composition comprising a) a polymer binder in the form of an aqueous emulsion of polymer particles and b) an anionic surfactant comprising at least one sulfonate group or its acid or salt form. The anionic surfactant b) cannot polymerize with the copolymer a). When the emulsion composition is fully or substantially or completely dried, a matrix is ​​provided for a granular electrode forming material, which generally includes an active material and a conductive material. Importantly, the aqueous emulsion binder composition comprising polymer particles a) and anionic surfactant b) has swelling resistance when contacted with a typical solvent used in a non-aqueous electrolyte of a secondary battery. Non-limiting examples of non-aqueous electrolytes are alkyl carbonates, linear dialkyl carbonates, ethers, or mixtures thereof. Non-limiting examples of specific such solvents include propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, or mixtures thereof.

[0030] Copolymer a)

[0031] As discussed in more detail below, the copolymer a) comprises, consists of, or consists essentially of a plurality of monomers as polymerized monomers. There are no particular restrictions on the selection of the polymerization method for the disclosed copolymer a). Any polymerization method can be used to synthesize the disclosed copolymer a). Non-limiting examples of polymerization methods can include solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, free radical polymerization, controlled polymerization, or ionic polymerization. In a preferred embodiment, the copolymer a) is prepared by free radical polymerization via emulsion polymerization.

[0032] The volume average particle size of the copolymer a) may be 30-500 nm, or may be a mixed particle size of various particle sizes of 30-500 nm. The volume average particle size is preferably in the range of 30-400 nm, more preferably in the range of 40-350 nm, even more preferably in the range of 50-300 nm. For example, the volume average particle size of the emulsified copolymer a) may be at least 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290 or at least 300 nm. The volume average particle size of the emulsified copolymer a) may be at most 500, 490, 480, 470, 460, 450, 440, 430, 420, 410, 400, 390, 380, 370, 360, 350, 340, 330, 320, 310 or at most 300 nm. As used herein, the volume average particle size is determined by dynamic light scattering (DLS) using a Nanotrac UPA150 from Microtrac.

[0033] The Tg of copolymer a) may be less than 55°C, preferably less than 45°C, more preferably less than 35°C, and most preferably less than 25°C. Thermal analysis using differential scanning calorimetry (DSC) can provide a convenient method to measure the glass transition temperature (Tg) of the dried copolymer a). Tests were performed using a standard heating rate of 10°C / min according to ATSM-D3418-15 (2018). Unless otherwise stated, the measured glass transition temperatures reported in this disclosure are measured during the second heating cycle. The glass transition temperatures reported herein are calculated using the Fox equation:

[0034]

[0035] Where Tg is the glass transition temperature of the copolymer, w i is the weight fraction of monomer i in the copolymer, Tg i is the glass transition temperature of the homopolymer of monomer i.

[0036] The minimum film forming temperature (MFFT) of the copolymer a) may be less than 25° C., preferably less than 20° C., and more preferably less than 15° C. The MFFT is determined according to ASTM-D2354-10 (2018) entitled “Standard Test Method for Minimum Film Formation Temperature (MFFT) of Emulsion Vehicles” to ensure the fluidity and ductility of the resin particles, thereby ensuring their ability to coalesce.

[0037] The number average molecular weight (Mn) of the copolymer a) may be at least 1,000 g / mol, preferably at least 5,000 g / mol, and more preferably at least 10,000 g / mol. Unless otherwise indicated, the number average molecular weight is measured by gel permeation chromatography using polymethyl methacrylate (PMMA) standards. If the copolymer a) is crosslinked, the sample is extracted with tetrahydrofuran (THF) and the extract is then dried. The dried extract portion of the sample is then tested for molecular weight and reported as Mn.

[0038] The copolymer a) comprises the following monomers as polymerized monomers: The amounts are expressed in weight percent, based on the dry weight of the copolymer a).

[0039] i) about 0.1-10% by weight of at least one ethylenically unsaturated ionic monomer comprising at least one functional group selected from the group consisting of phosphate, phosphonate; or acid or salt form thereof;

[0040] ii) about 0.1 to 10 weight percent of at least one ethylenically unsaturated ionic monomer comprising at least one sulfonate group or an acid or salt form thereof;

[0041] iii) about 80 to 99.8 weight percent of at least one nonionic monoethylenically unsaturated monomer;

[0042] iv) optionally about 0-10 weight percent of at least one ethylenically unsaturated ionic monomer comprising at least one functional group selected from the group consisting of a carboxylate, or an acid or salt or anhydride form thereof; and

[0043] v) optionally from about 0 to about 2 weight percent of at least one monomer containing at least two degrees of ethylenic unsaturation.

[0044] i) Ethylenically unsaturated ionic monomers

[0045] The copolymer a) comprises as polymerized monomers about 0.1-10 wt.% of at least one ethylenically unsaturated ionic monomer i) comprising at least one functional group selected from the group consisting of a phosphate group, a phosphonate group; or an acid or salt form thereof. The ionic monomer i) may comprise at least one of a phosphate ester of a polyalkylene glycol mono(meth)acrylate, a polyalkylene glycol allyl ether phosphate, vinylphosphonic acid, 2-(methacryloyloxy)ethylphosphonic acid; or an acid or salt or anhydride form thereof; or a mixture thereof.

[0046] %, 8.0, 8.2, 8.4, 8.6, 8.8, or at least about 9.0 weight percent of ethylenically unsaturated ionic monomer i), based on the total dry weight of copolymer a). The copolymer a) may comprise up to about 10.0, 9.9, 9.8, 9.7, 9.6, 9.5, 9.4, 9.3, 9.2, 9.1, 9.8, 8.8, 8.6, 8.4, 8.2, 8.0, 7.8, 7.6, 7.4, 7.2, 7.0, 6.8, 6.6, 6.4, 6.2, 6.0, 5.8, 5.6, 5.4, 5.2, 5.0, 4.8, 4.6, 4.4, 4.2, 4.0, 3.8, 3.6, 3.4, 3.2, 3.0, 2.8, 2.6, 2.4, 2.2, 2.0, 1.8, 1.6, 1.4, 1.2, or up to about 1.0 weight percent of ethylenically unsaturated ionic monomer i), based on the total dry weight of copolymer a).

[0047] ii) Ethylenically unsaturated ionic monomers

[0048] The copolymer a) further comprises about 0.1-10 wt% of at least one ethylenically unsaturated ionic monomer comprising at least one sulfonate group or its acid or salt form. The ethylenically unsaturated ionic monomer ii) may include at least one of 2-acrylamido-2-methylpropanesulfonic acid, 4-styrenesulfonic acid, vinylsulfonic acid, 2-sulfoethyl methacrylate, sulfoethyl acrylate, sulfopropyl methacrylate, sulfopropyl acrylate; their acid and / or salt forms; and mixtures thereof.

[0049] According to one embodiment, the ionic monomers i) and ii) may comprise a single ionic monomer comprising at least one functional group selected from phosphate, phosphonate; or its acid or salt form; and at least one sulfonate group or its acid or salt form. If present, the copolymer a) comprises 0.2-20 wt% of the single ionic monomer.

[0050] The copolymer a) may comprise at least about 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.2, 1.4, 1.6, 1.8, 2.0, 2.2, 2.4, 2.6, 2.8, 3.0, 3.2, 3.4, 3.6, 3.8, 4.0, 4.2, 4.4, 4.6, 4.8, 5.0, 5.2, 5.4, 5.6, 5.8, 6.0, 6.2, 6.4, 6.6, 6.8, 7.0, 7.2, 7.4, 7.6, 7.8, 8.0, 8.2, 8.4, 8.6, 8.8, 9.0, 9.2, 9.4, 9.6, 9.8, 10.0, 10.2, 10.4, 10.6, 10.8, 11.0, 11.2, 11.4, 11.6, 11.8, 12.0, 12.2, 12.4, 12.6, 12.8, 13.0, 13.2, 13.4, 13.6, 13.8, 14.0, 14.2, 14.4, 14.6, 14.8, 15.0, 15.2, 15.4, 15.6, 15.8, 16.0, 16.2, 16.4 , 16.6, 16.8, 17.0, 17.2, 17.4, 17.6, 17.8, 18.0, 18.2, 18.4, 18.6, 18.8 or at least about 19.0 weight percent of a single ionic monomer, wherein the ionic monomer comprises at least one functional group selected from phosphate, phosphonate; or an acid or salt form thereof; and at least one sulfonate group or an acid or salt form thereof.The copolymer a) may comprise up to about 20.0, 19.9, 19.8, 19.7, 19.6, 19.5, 19.4, 19.3, 19.2, 19.1, 19.0, 18.8, 18.6, 18.4, 18.2, 18.0, 17.8, 17.6, 17.4, 17.2, 17.0, 16.8, 16.6, 16. 4, 16.2, 16.0, 15.8, 15.6, 15.4, 15.2, 15.0, 14.8, 14.6, 14.4, 14.2, 14.0, 13.8, 13.6, 13.4, 13.2, 13.0, 12.8, 12.6, 12.4, 12.2, 12.0, 11.8, 11.6, 11.4, 11.2, 11.0, 10.8, 1 0.6, 10.4, 10.2, 10.0, 9.9, 9.8, 9.7, 9.6, 9.5, 9.4, 9.3, 9.2, 9.1, 9.0, 8.8, 8.6, 8.4, 8.2, 8.0, 7.8, 7.6, 7.4, 7.2, 7.0, 6.8, 6.6, 6.4, 6.2, 6.0, 5.8, 5.6, 5.4, 5.2, 5.0, 4.8, 4.6, 4.4, 4.2, 4.0, 3.8, 3.6, 3.4, 3.2, 3.0, 2.8, 2.6, 2.4, 2.2, 2.0, 1.8, 1.6, 1.4, 1.2 or up to about 1.0 weight percent of a single ionic monomer comprising at least one functional group selected from phosphate, phosphonate; or their acid or salt form; and at least one sulfonate group or their acid or salt form.

[0051] iii) Nonionic monoethylenically unsaturated monomers

[0052] The copolymer a) comprises about 80-99.8% by weight of at least one nonionic monoethylenically unsaturated monomer iii). Non-limiting examples of suitable monomers iii) are water-insoluble lower alkyl esters of (meth)acrylic acid or other acids and / or associative monomers containing hydrophobic groups, such as hydrophobically modified polyoxyalkylene esters and monomers containing nonionic groups. Suitable nonionic ethylenically unsaturated monomers iii) include, but are not limited to, acrylates and methacrylates, such as C1 to C12 (meth)acrylates, (meth)acrylamide, (meth)acrylonitrile, vinyl acetate, styrene and its derivatives, diisobutylene, vinylpyrrolidone, vinylcaprolactam and mixtures thereof.

[0053] According to one embodiment, the nonionic monoethylenically unsaturated monomer iii) comprises at least one of C1 to C12 (meth) alkyl acrylate, styrene or its derivatives, vinyl acetate, vinyl versatate, (meth) acrylamide, (meth) acrylonitrile or its derivatives, diisobutylene, vinyl pyrrolidone, vinyl caprolactam, or a mixture thereof. The nonionic monoethylenically unsaturated monomer iii) is preferably styrene, methyl (meth) acrylate, ethyl (meth) acrylate, propyl (meth) acrylate, butyl (meth) acrylate, 2-ethylhexyl (meth) acrylate, octyl (meth) acrylate, decyl (meth) acrylate, and lauryl (meth) acrylate, more preferably styrene, butyl (meth) acrylate, 2-ethylhexyl (meth) acrylate, octyl (meth) acrylate, decyl (meth) acrylate, and lauryl (meth) acrylate.

[0054] According to some embodiments, the copolymer a) comprises as polymerized monomers 80-99.8 wt. % of at least one nonionic monoethylenically unsaturated monomer iii), preferably 90-99.8 wt. % and more preferably 95-99 wt. % of at least one nonionic monoethylenically unsaturated monomer iii).

[0055] According to certain embodiments, the copolymer a) comprises as polymerized monomers at least 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97 or at least 98 weight % of at least one nonionic monoethylenically unsaturated monomer iii). According to some embodiments, the copolymer a) comprises as polymerized monomers at most 99.8, 99, 98, 97, 96, 95, 94, 93, 92, 91, 90 or at most 89 weight % of at least one nonionic monoethylenically unsaturated monomer iii).

[0056] iv) Ethylenically unsaturated ionic monomers

[0057] According to one embodiment, the copolymer a) may optionally contain monomer iv) as a polymerized monomer, which contains at least one functional group containing a carboxylate or its acid or salt or anhydride form. The monomer iv) may contain at least one of (meth)acrylic acid, 2-carboxyethyl acrylate, 2-polycarboxyethyl acrylate, itaconic acid monoester, maleic acid, fumaric acid, crotonic acid, itaconic acid; or its acid or salt or anhydride form; or a mixture thereof. Preferably, monomer iv) is (meth)acrylic acid, itaconic acid, 2-carboxyethyl acrylate or maleic acid, fumaric acid, more preferably (meth)acrylic acid, itaconic acid or 2-carboxyethyl acrylate.

[0058] If present, copolymer a) comprises as polymerized monomers about 0-10 wt. % (based on the dry weight of copolymer a)) of at least one monomer iv) comprising a carboxylate or an acid or salt or anhydride form thereof. According to some embodiments, the copolymer a) comprises at least about 0.05, 0.1, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5 or at least about 8.0 wt. % of monomer iv) based on the dry weight of copolymer a). According to some embodiments, the copolymer a) comprises up to about 10.0, 9.5, 9.0, 8.5, 8.0, 7.5, 7.0, 6.5, 6.0, 5.5, 5.0, 4.5, 4.0, 3.5, 3.0, 2.5, 2.0, 1.5 or up to about 1.0 wt. % of monomer iv) as polymerized monomer, based on the dry weight of copolymer a).

[0059] v) Monomers containing at least two ethylenic unsaturations

[0060] According to one embodiment, the copolymer a) may optionally comprise as polymerized monomer a monomer v) comprising at least two ethylenic unsaturations. If present, the monomer v) may be present in the copolymer a) at about 0-2 wt. %, based on the dry weight of the copolymer a). According to some embodiments, the monomer v) comprises at least one of the following: allyl ether obtained from a polyol; an acrylate or methacrylate obtained from a polyol; divinylnaphthalene; trivinylbenzene; 1,2,4-trivinylcyclohexane; triallyl pentaerythritol, diallyl pentaerythritol; diallyl sucrose; trimethylolpropane diallyl ether; 1,6-hexanediol di(meth)acrylate; allyl (meth)acrylate; diallyl itaconate; diallyl fumarate; diallyl maleate; butanediol dimethacrylate; ethylene glycol di(meth)acrylate; polyethylene glycol di(meth)acrylate; trimethylolpropane tri(meth)acrylate; methylenebis(meth)acrylamide; triallyl cyanurate; diallyl phthalate; divinylbenzene; or a mixture thereof. If present, the monomer v) is preferably 1,6-hexanediol di(meth)acrylate; allyl (meth)acrylate; diallyl itaconate; ethylene glycol di(meth)acrylate; polyethylene glycol di(meth)acrylate; diallyl phthalate; divinylbenzene; or a mixture thereof, more preferably 1,6-hexanediol di(meth)acrylate; allyl (meth)acrylate; ethylene glycol di(meth)acrylate; diallyl phthalate; divinylbenzene; or a mixture thereof.

[0061] According to some embodiments, the copolymer a) may comprise as a polymerized monomer at least 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7 or at least 1.8 wt.-% of monomer v), based on the total dry weight of the copolymer a). According to some embodiments, the copolymer a) may comprise as a polymerized monomer at least 2.0, 1.9, 1.8, 1.7, 1.6, 1.5, 1.4, 1.3, 1.2, 1.1, 1.0, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, 0.1 wt.-% of monomer v), based on the total dry weight of the copolymer a).

[0062] b) Anionic surfactants

[0063] The aqueous emulsion composition comprises about 0.5-5 wt. % of at least one anionic surfactant b) comprising at least one sulfonate group or its acid or salt form, based on the dry weight of the copolymer a). The anionic surfactant b) is not polymerizable with the copolymer a).

[0064] As used herein, "polymerizable" refers to a compound or composition having at least one unsaturated carbon-carbon bond that can undergo free radical polymerization. As used herein, "non-polymerizable" refers to a compound or composition lacking the unsaturated carbon-carbon bond.

[0065] The anionic surfactant b) comprises at least one of alkyl sulfonate, alkylbenzene sulfonate, alkyl diphenyl oxide disulfonate; or its acid or salt form; or a mixture thereof. Non-limiting examples include linear alkylbenzene sulfonic acid, sodium lignin sulfonate, sodium alkyl sulfonate, calcium lignin sulfonate, sodium alkylbenzene sulfonate, disodium methylene bisnaphthalene sulfonate, sodium C14-16 alkyl sulfonate; or its acid or salt form; or a mixture thereof. Preferably, the anionic surfactant is alkyl diphenyl oxide disulfonate; or its acid or salt form. Dowfax TM 2A1 (The Dow Chemical Company) is a commercially available surfactant of this type.

[0066] The anionic surfactant b) is present in the aqueous emulsion composition in an amount of about 0.5-5 wt % based on the dry weight of the copolymer a). According to some embodiments, the aqueous emulsion composition may comprise at least 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7. 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7 or 4.8 wt % of anionic surfactant b) based on the dry weight of the copolymer a). According to some embodiments, the aqueous emulsion composition may comprise up to 5.0, 4.9, 4.8, 4.7, 4.6, 4.5, 4.4, 4.3, 4.2, 4.1, 4.0, 3.9, 3.8, 3.7, 3.6, 3.5, 3.4, 3.3, 3.2, 3.1, 3.0, 2.9, 3.8, 3.7, 3.6, 3.5, 3.4, 3.3, 3.2, 3.1, 3.0, 2.9, 2.8, 2.7, 2.6, 2.5, 2.4, 2.3, 2.2, 2.1, 2.0, 1.9, 1.8, 1.7, 1.6, 1.5, 1.4, 1.3, 1.2, 1.1 or up to 1.0 wt. % of anionic surfactant b), based on the dry weight of copolymer a).

[0067] Swelling

[0068] The aqueous emulsion composition disclosed herein resists swelling when in contact with a non-aqueous solvent used in a secondary battery. According to one embodiment, a film of an aqueous emulsion composition having a thickness of 1±0.3 mm is exposed to a mixed battery solvent at 60°C for three days, and the swelling is less than 120%, wherein the mixed battery solvent is composed of ethylene carbonate, diethyl carbonate, and dimethyl carbonate in a weight ratio of 1:1:1. The swelling degree is expressed as W1 / W0×100, where W0 is the weight of the film before exposure to the solvent and W1 is the weight of the film after exposure to the solvent. According to some embodiments, after being exposed to a mixed battery solvent (composed of ethylene carbonate, diethyl carbonate, and dimethyl carbonate in a weight ratio of 1:1:1) at 60°C for three days, the swelling degree may be less than 119%, 118%, 117%, 116%, 115%, 114%, 113%, 112%, 111%, or less than 110%.

[0069] Slurry formed from aqueous emulsion composition

[0070] A slurry composition for forming an electrode of a non-aqueous secondary battery is provided, wherein the slurry composition comprises the aqueous emulsion composition and at least one particulate electrode-forming material.

[0071] The granular electrode forming material comprises a granular active material and conductive particles that are bound together (physically and / or chemically) by an aqueous emulsion composition. The active material is a material that can embed lithium ions, i.e., a material that can absorb / release lithium ions. Such active materials are known in the art. Conductive particles are also known in the art and are materials that can conduct electrons. Certain materials can perform both functions in an electrode.

[0072] The granular electrode forming material may include, but is not limited to, conductive carbon additives, carbon nanotubes (CNTs), synthetic graphite, natural graphite, hard carbon, activated carbon, carbon black, graphene, mesoporous carbon, amorphous silicon, semi-crystalline silicon, silicon oxide, silicon nanowires, tin, tin oxide, germanium, lithium titanate, mixtures or composites of the above materials and / or other materials known in the art or described herein suitable for use as electrodes in lithium ion batteries. These particles may include active materials, i.e., materials capable of embedding (accepting) lithium ions, and conductive materials. After drying, the electrode film of the lithium ion capacitor and / or lithium ion battery may contain about 80% by weight, preferably up to 94, and more preferably up to 98% by weight of the granular electrode forming material. These electrode forming materials a) are typically in the form of solid powders.

[0073] Conductive carbon materials (such as carbon black and graphite powder) are widely used in positive and negative electrodes to reduce the internal resistance of electrochemical systems. Non-limiting examples of conductive carbon may include furnace black, acetylene black, CNT, fine graphite powder, vapor deposited graphite fiber and Ketjen carbon black. The typical loading level of conductive carbon relative to active material in the electrode forming material is generally in the range of 0.1% to 20% by weight of the total amount of granular electrode forming material, and more preferably in the range of 0.5% to 10% by weight.

[0074] The amount of particulate electrode forming material (including both active material and conductive carbon) present in the electrode forming slurry composition may be 50 to 99 weight percent, preferably 80 to 98 and most preferably 94 to 98 weight percent of the total dry weight of the slurry composition.

[0075] According to one embodiment, at least one granular electrode forming material includes at least one of the following: furnace black, acetylene black, Ketjen black, carbon nanotubes (CNTs), synthetic graphite, natural graphite, hard carbon, activated soft carbon, carbon black, graphene, mesoporous carbon, amorphous silicon, semi-crystalline silicon, silicon oxide, silicon nanowires, tin, tin oxide, germanium, lithium titanate; or a mixture or composite thereof.

[0076] Other additives

[0077] As known and used in the art, other additives may be optionally included in the slurry composition. Importantly, these optional additives are in addition to the anionic surfactant b) described above. These optional additives include wetting agents, anti-settling agents, dispersants, adhesion promoters, coalescing agents, rheology modifiers, anti-settling agents, surfactants and mixtures thereof.

[0078] Surfactant and / or anti-settling agent can be added to aqueous composition with 0 to 10 parts per 100 parts of water, preferably 0.1 to 10 parts, more preferably 0.5 to 5 parts. These anti-settling agents or surfactants are added to aqueous composition after polymerization, usually to improve storage stability, and provide additional stability in slurry preparation process. Some surfactants / anti-settling agents may also be present in aqueous composition remaining during polymerization. Useful anti-settling agents include but are not limited to ionic surfactants, such as alkyl sulfates (such as sodium lauryl sulfate and ammonium lauryl sulfate), carboxylates, phosphates, phosphonates (such as those sold by DuPont under the CAPSTONE brand name) and non-ionic surfactants, such as TRITON X series (from Dow) and Pluronic (PLURONIC) series (from BASF). In one embodiment, only anionic surfactants are used. It is preferred that there is no fluorinated surfactant in aqueous composition, whether it is residual surfactant from polymerization process, or surfactant added after polymerization when forming or concentrating aqueous dispersion.

[0079] The wetting agent can be added to the aqueous composition in an amount of 0 to 5 parts per 100 parts of water, preferably 0 to 3 parts. Surfactants can act as wetting agents, but wetting agents can also include non-surfactants. In some embodiments, the wetting agent can be an organic solvent. Useful wetting agents include, but are not limited to, ionic and non-ionic surfactants, such as TRITON TM series (from Dow) and series (from BASF) and organic liquids that are compatible with the aqueous composition, including but not limited to N-methyl-2-pyrrolidone (NMP), dimethyl sulfoxide (DMSO) or acetone.

[0080] Thickeners and rheology modifiers may be present in the aqueous composition at 0 to 10 parts, preferably 0 to 5 parts, per 100 parts of water. Adding a water-soluble thickener or rheology modifier to the aqueous composition can prevent or slow down the settling of the inorganic powder material while providing a suitable slurry viscosity for the coating process. Useful thickeners include, but are not limited to, ACRYSOL TM series (from Dow Chemical); RHEOTECH TM Series (from Gotech), VISCOATEX TM series (from Coatex), partially neutralized poly(acrylic acid) or poly(methacrylic acid), such as from Lubrizol Or from Gaotai 100N; and carboxylated alkyl cellulose, such as carboxymethyl cellulose (CMC). Adjusting the pH of the aqueous composition can increase the effectiveness of some thickeners. In addition to organic rheology modifiers, inorganic rheology modifiers can also be used alone or in combination. Useful inorganic rheology modifiers include, but are not limited to, natural clays (such as montmorillonite and bentonite), artificial clays (such as laponite), and other clays (such as silica) and talc.

[0081] The optional fugitive adhesion promoter helps to create the desired interconnectivity in the coating formed from the composition of the present invention. As used herein, "fugitive adhesion promoter" refers to an agent that increases the interconnectivity of the composition after coating. The fugitive adhesion promoter can then be removed from the formed substrate, typically by evaporation (for chemicals) or by dissipation (for increased energy).

[0082] The fugitive adhesion promoter can be a chemical material, an energy source combined with pressure, or a combination thereof, used in an effective amount to cause interconnection of the components of the aqueous composition during electrode formation. For chemical fugitive adhesion promoters, the composition contains 0 to 150 parts, preferably 0 to 100 parts, and more preferably 0 to 30 parts of one or more fugitive adhesion promoters per 100 parts of water. Preferably, this is an organic liquid that is soluble in water or miscible with water. This organic liquid acts as a plasticizer or coalescing agent for the acrylic particles, making them sticky and able to act as discrete adhesion points in the drying step. The binder particles are able to soften, flow and adhere to the powder material during the drying stage, thereby forming an electrode with irreversible high connectivity. In one embodiment, useful inorganic solvents or coalescing agents include but are not limited to Texanol TM (Eastman), Optifilm TM 400 (Eastman), Velate TM 368 (Eastman), Butyl Carbitol TM (Dow), Dowanol TM DPM (Dow), 4(Vantulus Specialty Chemicals), Benzoflex TM 50(Eastman) CA5310 (BASF).

[0083] application

[0084] The slurry composition can be used as an active layer or coating on an electrode (e.g., an anode for use in an electrical energy storage device). Also disclosed is an electrode (e.g., an anode) made of a current collector coated with a dry form of the electrode-forming slurry composition disclosed herein on at least one surface, such that the thickness of the electrode (e.g., an anode) is at least 10 microns.

[0085] The electrode (e.g., anode) can be used in an energy storage device containing a non-aqueous electrolyte. The energy storage device includes at least one electrode (e.g., anode) made of a current collector coated with a dry form of the electrode-forming slurry composition disclosed herein on at least one surface. The energy storage device is selected from the group consisting of a non-aqueous battery, a capacitor, and a membrane electrode assembly.

[0086] Provided is an electrode assembly for a non-aqueous secondary battery, comprising at least one conductive substrate having the slurry composition coated on its surface. Advantageously, the electrode assembly is an anode or a cathode, preferably an anode.

[0087] Example

[0088] Evaluation Methodology:

[0089] Binder's resistance to swelling by battery solvents

[0090] First, a polymer binder in latex form is dried at a temperature of 23°C to 25°C to form a film with a thickness of 1±0.3 mm. The resulting film is further dried in an oven at 110°C for 2 hours. About 0.6 g of the dried film is cut and weighed. At 60°C, a membrane with an initial weight of W0 is immersed in a mixed battery solvent (the weight ratio of ethylene carbonate / diethyl carbonate / dimethyl carbonate is 1:1:1) for 3 days to swell it. Then, the membrane is removed from the solvent, and its mass is measured after wiping off the solvent on the surface of the membrane with a low-dust wipe (Kimwipe). The mass of the swollen membrane is recorded as W1. The degree of swelling in the battery solvent is calculated using the following calculation formula: Swelling % = W1 / W0×100. For battery applications, the swelling % is preferably less than 120%.

[0091] Example 1: Production of adhesive

[0092] A 1-gallon reactor was charged with 534 g of deionized water and 0.9 g of Then, 16.2 g of Sipomer PAM 4000 (ethyl methacrylate phosphate), 400.4 g of 2-ethylhexyl acrylate, 436.1 g of styrene, 36.1 g of methyl methacrylate, and 18.0 g of sodium 4-vinylbenzene sulfonate were weighed into the first glass beaker and mixed with 5.9 g of A-246MBA and 365 g of deionized water were mixed to prepare a monomer pre-emulsion. Then 2.2 g of ammonium persulfate was weighed into a second glass beaker and dissolved in 15 g of deionized water to prepare an initial initiator. Subsequently, 1.0 g of ammonium persulfate was dissolved in 32.0 g of water in a third beaker to prepare a delayed initiator. The contents of the reactor were heated to a temperature of 83 ± 2 °C. Thereafter, 63.9 g of the monomer pre-emulsion and the initial initiator were first introduced into the reactor. After the reaction exotherm reached a peak, the remaining monomer pre-emulsion and the delayed initiator were fed into the reactor while maintaining the reactor temperature at 90 ± 2 °C. The delayed initiator was fed into the reactor within 260 minutes. The monomer pre-emulsion was fed into the reactor in 4 stages. Then 303.5 g of the monomer pre-emulsion was fed into the reactor within 45 minutes, followed by a 15 minute pause. The remaining monomer pre-emulsion was then added to the reactor in three stages according to the same feed profile. After the delayed initiator feed was completed within 260 minutes, the contents of the reactor were boiled for 30 minutes and then the mixture was cooled to 70°C. During the 30-minute boil, a post-oxidant solution containing 2.6 g of 70% tert-butyl hydroperoxide and 23.3 g of deionized water was prepared in a glass beaker. A solution containing 1.8 g of FF6M (reducing agent) and 45g of post-reducing agent solution of deionized water. Then after 30 minutes of boiling time, the post-oxidant and post-reducing agent solutions were fed into the reactor over 75 minutes. The mixture was allowed to cool and then filtered. Then 500g of the filtered latex was weighed into a separate beaker. Under stirring, 5.1g of Dowfax TM 2A1 (anionic surfactant b)) was added in one portion to 500 g of the filtered latex in a beaker. The mixed blend was Example 1.

[0093] Comparative Example 1 :Manufacturing of adhesives

[0094] In Example 1, Dowfax was not added. TM The latex of 2A1 (anionic surfactant b)) was used as Comparative Example 1.

[0095] Example 2

[0096] A 1-gallon reactor was charged with 490 g of deionized water and 0.9 g of Then, 16.2 g Sipomer PAM 4000, 384.0 g 2-ethylhexyl acrylate, 436.1 g styrene, 36.1 g methyl methacrylate, 18.0 g sodium 4-vinylbenzenesulfonate, 16.4 g methacrylic acid were weighed into the first glass beaker and mixed with 5.9 g A-246MBA, 21.1g FES32 (fatty alcohol polyglycol ether sulfate, sodium salt) and 348g of deionized water were mixed to prepare a monomer pre-emulsion. Then, 2.2 grams of ammonium persulfate were weighed into a second glass beaker and dissolved in 15g of deionized water to prepare an initial initiator. Then, 1.0g of ammonium persulfate was dissolved in 32.0g of water in a third beaker to prepare a delayed initiator. The contents of the reactor were heated to a temperature of 83±2°C. Then, 64.1g of the monomer pre-emulsion and the initial initiator were first introduced into the reactor. After the reaction exotherm reached a peak, the remaining monomer pre-emulsion and the delayed initiator were fed into the reactor while maintaining the reactor temperature at 90±2°C. The delayed initiator was fed into the reactor within 260 minutes. The monomer pre-emulsion was fed into the reactor in 4 stages. Then 304.5g of the monomer pre-emulsion was fed into the reactor within 45 minutes, followed by a 15 minute pause in the feed. The remaining monomer pre-emulsion was then fed into the reactor in three stages following the same feed profile. After the delayed initiator feed was completed over 260 minutes, the contents of the reactor were boiled for 30 minutes and the mixture was then cooled to 70°C. During the 30-minute boiling process, a post-oxidant solution containing 2.6 g of 70% tert-butyl hydroperoxide and 23.3 g of deionized water was prepared in a glass beaker. A post-oxidant solution containing 1.8 g of t-butyl hydroperoxide was also prepared in a glass beaker. FF6M and 45g of post-reducing agent solution of deionized water. After 30 minutes of boiling, 13.0g of 14 wt% ammonia was added to the reactor at one time. The post-oxidant and post-reducing agent solutions were then fed into the reactor over 45 minutes. The mixture was cooled and filtered. 500g of the filtered latex was weighed into a separate beaker. Then, under stirring, 5.2g of Dowfax TM 2A1 was added to 500 g of the filtered latex in one portion. The mixed blend was Example 2.

[0097] Comparative Example 2

[0098] In Example 2, Dowfax was not added. TM The latex of 2A2 was used as Comparative Example 2.

[0099] Example 3

[0100] A 1-gallon reactor was charged with 450 g of deionized water and 0.9 g of Then, 16.2 g Sipomer PAM 4000, 384.0 g 2-ethylhexyl acrylate, 436.1 g styrene, 36.1 g methyl methacrylate, 18.0 g sodium 4-vinylbenzenesulfonate, 16.4 g methacrylic acid were weighed into the first glass beaker and mixed with 5.9 g A-246MBA, 14.0g Dowfax TM 2A1 and 348g of deionized water were mixed to prepare a monomer pre-emulsion. Then, 2.2 grams of ammonium persulfate were weighed into a second glass beaker and dissolved in 15g of deionized water to prepare an initial initiator. Then, 1.0g of ammonium persulfate was dissolved in 32.0g of water in a third beaker to prepare a delayed initiator. The contents of the reactor were heated to a temperature of 83±2°C. Then, 63.8g of the monomer pre-emulsion and the initial initiator were first introduced into the reactor. After the reaction exotherm reached a peak, the remaining monomer pre-emulsion and the delayed initiator were fed into the reactor while maintaining the reactor temperature at 90±2°C. The delayed initiator was fed into the reactor within 260 minutes. The monomer pre-emulsion was fed into the reactor in 4 stages. Then 302.8g of the monomer pre-emulsion was fed into the reactor within 45 minutes, followed by a 15 minute pause. Then the remaining monomer pre-emulsion was fed into the reactor in three stages according to the same feed profile. After the delayed initiator feed was completed within 260 minutes, the contents of the reactor were boiled for 30 minutes and the medium was then cooled to 70°C. During the 30-minute boil, a post-oxidant solution containing 2.6 g of 70% tert-butyl hydroperoxide and 23.3 g of deionized water was prepared in a glass beaker. A solution containing 1.8 g of FF6M and 45g of post-reducing agent solution of deionized water. After 30 minutes of boiling, 15.0g of 14 wt% ammonia was added to the reactor at one time. The post-oxidant and post-reducing agent solutions were then fed into the reactor over 45 minutes. The mixture was cooled and filtered.

[0101] Comparative Example 3

[0102] The samples were prepared in the same manner as in Example 1, except that the monomer selection and ratio were different. Table 1 lists the weight percentage of each monomer relative to the total amount of monomers used. In addition, Comparative Example 3 also did not contain Dowfax TM 2A1 (anionic surfactant b)) was added as a post addition.

[0103] Comparative Example 4

[0104] The samples were prepared in the same manner as in Example 1, except that the monomer selection and ratio were different. Table 1 lists the weight percentage of each monomer relative to the total amount of monomers used. In addition, Comparative Example 4 also did not contain Dowfax TM 2A1 (anionic surfactant b)) was added as a post addition.

[0105]

[0106] Comparing Example 1 and Comparative Example 1 in Table 1, the Dowfax TM The sulfonate surfactant of 2A1 (anionic surfactant b)) significantly improved the swelling percentage of the polymer from 130% (Comparative Example 1) to 112% (Example 1) because lower swelling percentages are more desirable. Similarly, the sulfonate-containing anionic surfactant b) also provided the same effect, as can be seen by comparing Example 2 (113%) with Comparative Example 2 (123%). In Comparative Examples 3 and 4, the two polymers that do not contain the required sulfonate monomer and the separately added surfactant have a larger swelling percentage in the battery solvent mixture. For binders for lithium-ion battery applications, a larger swelling percentage is undesirable. In Example 3, the polymer containing the required sulfonate monomer, the separately added sulfonate surfactant, and optional methacrylic acid has the best (lowest) swelling percentage.

[0107] Abbreviations in Table 1:

[0108] Sty=Styrene

[0109] 2EHA=2-Ethylhexyl acrylate

[0110] MMA = Methyl Methacrylate

[0111] PAM = Phosphoethyl methacrylate (Ethyl methacrylate phosphate)

[0112] NaSS = Sodium 4-styrene sulfonate

[0113] MAA = Methacrylic Acid

[0114] DVB = divinylbenzene

[0115] A 246MBA, α-olefin sulfonic acid sodium salt, surfactant

[0116] FES 32, Fatty alcohol ether sulfate sodium salt, surfactant

[0117] 2A1=DOWFAX TM 2A1, Alkyl diphenyl ether disulfonate surfactant, Surfactant

[0118] Example 1: Preparation of slurry

[0119] Seven 6.5 mm zirconium oxide balls were placed in a 125 mL container of a Thinky ARE-310. Then, 0.3 g of carbon black [Super P-Li from Timcal] plus 4.5 g of 1.5% solid carboxymethyl cellulose (CMC) solution [Ashland Bondwell BVH9] and 13 g of graphite (15 μm) were added and mixed at 2000 rpm for 2 minutes. Then, 3.5 g of CMC solution was added and mixed at 2000 rpm for 2 minutes, followed by multiple incremental additions of CMC solution and mixing to reach a total CMC solution addition of 11.2 g. Then, 2.8 g of the Example 1 emulsion in Table 1 was added and mixed at 2000 rpm for 2 minutes, twice. The slurry exhibited a smooth creamy character and had about 50% solids by weight.

[0120] Example 2: Preparation of electrodes:

[0121] The slurry prepared in Example 1 was cast onto copper foil with a wet thickness of approximately 110 μm using a 5 mil square frame coater from BYK. The cast electrode was placed in a 120°C convection oven for 30 minutes and then rolled at room temperature to achieve a porosity of approximately 20% by volume. The porosity of the electrode was calculated back from its expected (weight contribution of each component) and the apparent density, which was obtained by measuring the weight and volume of the electrode using a micrometer and a balance to 5 decimal places.

Claims

1. An aqueous emulsion composition for non-aqueous battery electrodes, the composition comprising: a) a copolymer comprising, based on the dry weight of the copolymer, as polymerized monomer: i) about 0.1-10% by weight of at least one ethylenically unsaturated ionic monomer comprising at least one functional group selected from the group consisting of phosphate, phosphonate; or acid or salt form thereof; ii) about 0.1 to 10 weight percent of at least one ethylenically unsaturated ionic monomer comprising at least one sulfonate group or an acid or salt form thereof; iii) about 80 to 99.8 weight percent of at least one nonionic monoethylenically unsaturated monomer; iv) optionally about 0-10 weight percent of at least one ethylenically unsaturated ionic monomer comprising at least one functional group selected from the group consisting of a carboxylate, or an acid or salt or anhydride form thereof; and v) optionally from about 0 to about 2 weight percent of at least one monomer containing at least two degrees of ethylenic unsaturation; and b) about 0.5 to 5 wt. %, based on the dry weight of copolymer a), of at least one anionic surfactant comprising at least one sulfonate group, or an acid or salt form thereof, wherein the anionic surfactant is not polymerizable with copolymer a).

2. The aqueous emulsion composition according to claim 1, wherein the anionic surfactant b) comprises at least one of an alkyl sulfonate, an alkylbenzene sulfonate, an alkyl diphenyl oxide disulfonate; or an acid or salt form thereof; or a mixture thereof.

3. The aqueous emulsion composition according to claim 1 or 2, wherein the monomer i) comprises at least one of polyalkylene glycol mono(meth)acrylate, polyalkylene glycol allyl ether phosphate, vinyl phosphonic acid, 2-(methacryloyloxy)ethylphosphonic acid; or its acid, salt or anhydride form; or a mixture thereof.

4. The aqueous emulsion composition according to any one of claims 1 to 3, wherein the monomer ii) comprises at least one of 2-acrylamide-2-methylpropanesulfonic acid, 4-styrenesulfonic acid, vinylsulfonic acid, 2-sulfoethyl methacrylate, sulfoethyl acrylate, sulfopropyl methacrylate, sulfopropyl acrylate; or a salt form thereof; or a mixture thereof.

5. The aqueous emulsion composition of claim 1, wherein the monomers i) and ii) comprise single ionic monomers, and the single ionic monomers contain both at least one functional group selected from phosphate, phosphonate; or their acid or salt form; and at least one sulfonate group or their acid or salt form; and wherein the copolymer a) contains 0.2-20 wt. % of the single ionic monomer.

6. The aqueous emulsion composition according to any one of claims 1 to 5, wherein the monomer iii) comprises at least one of C1 to C12 (meth) alkyl acrylate, styrene or derivatives thereof, vinyl acetate, vinyl versatate, (meth) acrylamide, (meth) acrylonitrile or derivatives thereof, diisobutylene, vinyl pyrrolidone, vinyl caprolactam; or a mixture thereof.

7. The aqueous emulsion composition according to any one of claims 1 to 6, wherein the monomer iv) comprises at least one of (meth)acrylic acid, 2-carboxyethyl acrylate, 2-polycarboxyethyl acrylate, itaconic acid monoester, maleic acid, fumaric acid, crotonic acid, itaconic acid; or its acid, salt or anhydride form; or a mixture thereof.

8. The aqueous emulsion composition according to any one of claims 1 to 7, wherein the monomer v) comprises at least one of the following: allyl ethers obtained from polyols; acrylates or methacrylates obtained from polyols; divinylnaphthalene; trivinylbenzene; 1,2,4-trivinylcyclohexane; triallyl pentaerythritol, diallyl pentaerythritol; diallyl sucrose; trimethylolpropane diallyl ether; 1,6-hexanediol di(meth)acrylate; allyl (meth)acrylate; diallyl itaconate; diallyl fumarate; diallyl maleate; butanediol dimethacrylate; ethylene glycol di(meth)acrylate; polyethylene glycol di(meth)acrylate; trimethylolpropane tri(meth)acrylate; methylenebis(meth)acrylamide; triallyl cyanurate; diallyl phthalate; divinylbenzene; or a mixture thereof.

9. The aqueous emulsion composition according to any one of claims 1 to 8, wherein the Tg of the copolymer a) is less than 55°C, preferably less than 45°C, more preferably less than 35°C, and most preferably less than 25°C, wherein the Tg is determined using the Fox equation.

10. The aqueous emulsion composition according to any one of claims 1 to 9, wherein the minimum film-forming temperature of the copolymer a) is less than 25°C, preferably less than 20°C, more preferably less than 15°C.

11. The aqueous emulsion composition according to any one of claims 1 to 10, wherein the copolymer a) comprises particles having a volume average particle size of 30 to 500 nm, preferably 30 to 400 nm, more preferably 40 to 350 nm, most preferably 50 to 300 nm.

12. The aqueous emulsion composition according to any one of claims 1 to 11, wherein the copolymer a) has a number average molecular weight of at least 1000 g / mol, preferably at least 5000 g / mol, more preferably at least 10,000 g / mol.

13. The aqueous emulsion composition according to any one of claims 1 to 12, wherein a film of the aqueous emulsion composition having a thickness of 1±0.3 mm has a swelling degree of less than 120% after being exposed to a mixed battery solvent at 60° C. for three days, wherein the mixed battery solvent consists of ethylene carbonate, diethyl carbonate and dimethyl carbonate in a weight ratio of 1:1:1; wherein, The swelling degree is expressed as W1 / W0×100, wherein W0 is the weight of the film before exposure and W1 is the weight of the film after exposure.

14. A slurry composition for forming an electrode of a non-aqueous secondary battery, the composition comprising: at least one particulate electrode-forming material; and The aqueous emulsion composition according to any one of claims 1 to 13.

15. The slurry composition of claim 14, wherein the at least one particulate electrode-forming material comprises at least one of furnace black, acetylene black, Ketjen black, carbon nanotubes (CNTs), synthetic graphite, natural graphite, hard carbon, activated soft carbon, carbon black, graphene, mesoporous carbon, amorphous silicon, semi-crystalline silicon, silicon oxide, silicon nanowires, tin, tin oxide, germanium, lithium titanate; or a mixture or composite thereof. 16 . An electrode assembly for a non-aqueous secondary battery, comprising a conductive substrate having the slurry composition of claim 14 or 15 coated on at least one surface thereof.

Citation Information

Patent Citations

  • Binder for battery binder solution, electrode mixture, electrode structure and battery

    JP1998298386A

  • Binder for lithium ion secondary battery electrodes, slurry obtained by using the binder for electrodes, electrodes obtained by using the slurry, and lithium ion secondary battery obtained by using the electrodes

    JP2011243464A

  • Binder resin composition for electrode for nonaqueous secondary battery

    JP2013168323A

  • Composition for binder for non-aqueous cell electrode, binder for non-aqueous cell electrode, composition for non-aqueous cell electrode, non-aqueous cell electrode, and non-aqueous cell

    US10957909B2

  • Aqueous copolymer dispersion and coating composition

    US20080269402A1